Fifty years of artisan entrepreneurship: A systematic literature review - Uswatun Hasanah; Badri Munir Sukoco; Elisabeth Supriharyanti; Wann-Yih Wu (Journal of Innovation and Entrepreneurship, 2023)
Culturally based products and businesses have become increasingly common, drawing attention to artisan entrepreneurship. A small number of studies have comprehensively reviewed artisan entrepreneurship in terms of its antecedents and consequences, as is examined in this study. Specifically, this research looked at the factors that contribute to successful artisan entrepreneurship, managing environmental dynamism, markets, and institutional pressures. This study focuses on developing antecedents and consequences that may be used as a reference for the development of artisan entrepreneurship. A systematic literature review was conducted on 72 papers from the last 50 years from the first quartile of the Scopus database. This study identified that environmental, social, organizational, and individual factors could determine the development of artisan entrepreneurship and have consequences on social, organizational, and individual levels. This framework may aid artisan entrepreneurship and stakeholders in identifying the factors needed in the development of artisan entrepreneurship. The main elements of the resulting research agenda include suggestions for theory development, methodology, antecedents, and consequences.
Keywords: 650; Innovation; Antecedents; Artisan entrepreneurship; Consequences; Cultural identity